Hubungan Kemampuan Awal dan Kepercayaan Diri dengan Prestasi Belajar Matematika pada Siswa Kelas V SDN 4 Rensing Tahun Pembelajaran 2016/2017 - Yuliana Susanti (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2018)
The purpose of this study is 1) Want to know the relationship of the initial ability of students in improving the achievement of learning Mathematics in grade V SDN 4 Rensing. 2) Want to know the relationship of students' self confidence in improving Mathematics learning achievement in grade V SDN 4 Rensing students. 3) Want to know the relationship of initial ability with confidence in the students of grade V SDN 4 Rensing. 4) Want to know the relationship of initial ability and confidence to the achievement of learning Mathematics in grade V SDN 4 Rensing year of learning 2016/2017. This research uses facto expo research.This study concludes that: 1) Initial ability correlates significantly with mathematics learning achievement. 2) Confidence is significantly related to mathematics learning achievement 3) Initial ability to relate significantly with confidence 4) The interaction of initial ability and confidence relationship is significantly related to mathematics learning achievement with contribution of 69.1%.